PENGARUH RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, CAPITAL ADEQUACY RATIO (RGEC) DAN BIAYA OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL (BOPO) TERHADAP KINERJA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) (Studi Empiris Pada Bank Umum Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2012-2015) - Uky Megawati, 14.05.62.0009; Indarti, MG. Kentris (Students' Journal of Accounting and Banking, 2017)
This study aims to test and analyze the effect of RGEC and BOPO on Bank Performance at Commercial Banks listed on the Indonesia Stock Exchange (IDX).The population of this study are Commercial Banks listed on Indonesia Stock Exchange (BEI) during 2012-2015 which report complete financial statements and published on Indonesia Capital Market Directory (ICMD) and idx website. The sample that entered in this research criterion is 122 bank by using purposive sampling method. Methods of data analysis in this study using multiple linear regression analysis with SPSS 20 program.. The results showed that the variable of Non Perfoming Loan (NPL), Good Corporate Governance (GCG), and Capital Adequancy Ratio (CAR) have a positive influence on Return On Asset (ROA), while Net Interest Margin (NIM) on Return On Asset (ROA), as well as Operational Expense / Operating Income (BOPO) which has a significant negative effect on Return On Assets (ROA), while Loan to Deposit Ratio (LDR) has no significant positive effect on Return On Assets (ROA).Keywords: Return On Asset (ROA), Non Performing Loan (NPL), Loan Deposit Ratio (LDR), Good Corporate Governance (GCG), Net Interest Margin (NIM), Capital Adequacy Ratio (CAR), Operating Expense to Operating Income